Pengaruh Kualitas Pelayanan terhadap Minat Beli Ulang Penumpang Lion Air Bandar Udara Yogyakarta International Airport - Rio Fany Syarifaiz Prasetyo; Rahimudin Rahimudin (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This Study aims to analyze how service quality affect repurchase interest of the customers Lion Air Airlines in Yogyakarta International Airport. The Population of this research is customers who already repurchase more than twice of Lion Air Airlines in Yogyakarta International Airport. The Sample is 60 respondents. The Data of this Study were collected with online questionnaires distributed to the respondents. The Result of this study concluded that quality service does have an affected on re-purchasing interest, and included how much affect quality service on re-purchase interest. Keywords: Service Quality, Re-Purchase Interest, Lion Air, Yogyakarta International Airport